Branch Campuses in China - Stanfield, David; Wang, Qi (International Higher Education, 2012)
A small number of Western institutions are attempting to create full-scale branch campuses in China, but unique requirements and environmental challenges may prevent them from reaching world-class status. Three characteristics of world-class universitiessufficient talent, adequate resources, and appropriate governanceare applied to examine the potential for full-scale branch campuses in China.